Effects of mental imagery technique in addition to conventional physical therapy to improve hand functions in chronic stroke patient - Iqra Mubeen; Ashfaq Ahmad; Waqar Afzal (Journal of the Pakistan Medical Association, 2021)
Objective: To find the effect of mental imagery and conventional physical therapy for the treatment of hand function in chronic stroke patients. Methods: A randomized controlled trial was conducted at Rana and Alvi welfare society. A sample of 50 stroke patients was selected and divided in two groups; group A (experimental) and group B (control). Inclusion and exclusion criteria were established and patients meeting inclusion criteria were included in the study. P value was set as 0.05. Group A was treated with conventional physical therapy combined with mental imagery whereas Group B was treated with conventional physical therapy alone. Wolf motor function test and action research arm test was used as outcome measures. Results: Group A consisted of 68% of females and 32% of males and group B comprised of 44% females and 32% males. Mean age of group A and B were 59.68 + 2.37 and 58.52 + 2.46 respectively. Mean duration (in months) of stroke for group A was 16.32+3.77 (minimum and maximum duration 13 and 23 months respectively). The stroke mean duration of group B was 16.00 +2.34 (minimum and maximum duration 13 and 20 months respectively). Both groups did not show significant difference at 5th week (P=0.721) whereas a significant difference was observed at 10th week (P=0.000) Conclusion: It was concluded that mental imagery technique in combination with conventional physical therapy is significantly effective to improve hand function among chronic stroke patients in comparison to conventional physical therapy alone. Continuous...